Analisis Pengaruh Persepsi Manfaat Dan Persepsi Kemudahan Terhadap Sikap Pengguna Sistem Online UNAI Menggunakan Metode TAM - Raymond Maulany; Brenda Claudya (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2018)
Online system that has the aim to improve efficiency, effectiveness of data management and for the benefit of decision making. Theoretically the Technology Acceptance Model (TAM) method is widely used in research to measure the success of information system acceptance based on users in using information systems. With this method used to analyze the acceptance of the Online System at the Adventist University of Indonesia. A sample of 95 respondents was used with a sampling technique that is purposive sampling and sample calculation using the Slovin formula. Data were collected through questionnaires and analytical techniques using multiple linear regression analysis. The purpose of this study are: (1) To determine the perception of benefits affect the attitude of users, (2) To determine the effect of perceived ease of influence on user attitudes. (3) To determine the effect of perceived usefulness and perceived convenience on user attitudes. The results showed that (1) the perceived benefits of the Online System partially did not affect the user's attitude, (2) the perceived ease of the Online System partially affected the user's attitude, and (3) simultaneously the perceived usefulness and ease of perception influenced the attitude of the Online System users.